2018
DOI: 10.1108/ijm-10-2018-0328
|View full text |Cite
|
Sign up to set email alerts
|

Skill mismatch comparing educational requirements vs attainments by occupation

Abstract: Purpose The purpose of this paper is to overcome the problems that skill mismatch cannot be measured directly and that demand side data are lacking. It relates demand and supply side characteristics by aggregating data from jobs ads and jobholders into occupations. For these occupations skill mismatch is investigated by focussing on demand and supply ratios, attained vis-à-vis required skills and vacancies’ skill requirements in relation to the demand-supply ratios. Design/methodology/approach Vacancy data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In addition to the online survey filled out by web visitors, an offline version is available in countries with low literacy rates, which are completed with the help of an interviewer. Previous research has found the WageIndicator dataset to be representative in terms of the distribution across industries (Fortanier, 2008) and employees' demographics, even though employees with a low level of literacy (i.e., with a low level of education, corresponding to a value of 0 for the Education variable in our sample) as well as employees over the age of 50 were found to be relatively underrepresented in the dataset (De Vries, Tijdens, & Steinmetz, 2016;Tijdens, Beblavý, & Thum-Thysen, 2018). While this is a limitation, it does not undermine the value of our study given that (a) key groupings in terms of both education and age levels are well represented in the dataset and thus in our sample; (b) we account for different levels of education and age/experience in our estimations; and (c) we are interested in the comparison of MNEs versus domestic firms' employees having similar education levels and age/experience.…”
Section: Limitations and Further Areas For Investigationmentioning
confidence: 83%
See 1 more Smart Citation
“…In addition to the online survey filled out by web visitors, an offline version is available in countries with low literacy rates, which are completed with the help of an interviewer. Previous research has found the WageIndicator dataset to be representative in terms of the distribution across industries (Fortanier, 2008) and employees' demographics, even though employees with a low level of literacy (i.e., with a low level of education, corresponding to a value of 0 for the Education variable in our sample) as well as employees over the age of 50 were found to be relatively underrepresented in the dataset (De Vries, Tijdens, & Steinmetz, 2016;Tijdens, Beblavý, & Thum-Thysen, 2018). While this is a limitation, it does not undermine the value of our study given that (a) key groupings in terms of both education and age levels are well represented in the dataset and thus in our sample; (b) we account for different levels of education and age/experience in our estimations; and (c) we are interested in the comparison of MNEs versus domestic firms' employees having similar education levels and age/experience.…”
Section: Limitations and Further Areas For Investigationmentioning
confidence: 83%
“…The ''WageIndicator'' project was initiated in the Netherlands in 1999 and is managed by the WageIndicator Foundation, a coalition of AIAS, the University of Amsterdam Institute for Labour Studies, and local trade unions in 92 countries, which aims to improve labor market access and transparency. Previous studies have compared wages reported in WageIndicator samples and the distribution of samples across industries to the data of national statistics offices and found no inconsistencies (Fortanier, 2008;Tijdens, Beblavý, & Thum-Thysen, 2018). A further, extensive explanation of the dataset, which is very suitable for our purposes, and its possibilities and limitations, can be found in the Appendix.…”
Section: The Samplementioning
confidence: 97%
“…The current demand for skills in robotics was analyzed using open-access job vacancy databases Indeed.com and hh.ru. Online job ads reflect the employer's views about an ideal candidate, provide actual and objective information, and are a prospective tool for measuring labor demand, investigating skill requirements in particular areas, and identifying skills mismatch (Beblavý et al, 2016;Štefánik, 2012;Tijdens et al, 2018). A search for resources containing representative selection of vacancies suitable for automated collection and processing of textual data was conducted in 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Employers who hire graduates attach considerable significance to skills possessed by the latter (Mawson and Haworth, 2018). Interestingly, skill mismatch refers to incongruity between an employee’s “educational and vocational attainments and the requirements of the job” (Tijdens et al , 2018). Since the 1970s, social scientists have been focussing their research on the potential gap between academic attainments of workers and the skills they actually use at work (Llorente et al , 2018).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%